European Multiculturalisms : Cultural, Religious and Ethnic Challenges - Triandafyllidou, Anna (Edinburgh University Press, 2022)
Proposes a common European intellectual framework to evaluate recent developments in European multiculturalismThe heightened security awareness in the wake of the 9/11 attacks and the London and Madrid bombings has resulted in a 'crisis of multiculturalism'. Now is the time to look at the renewed challenges that multiculturalism faces today.Each chapter in this interdisciplinary book reviews the actual state of affairs in several countries in relation to the theories behind immigrant minority claims. With a special focus on Muslim immigrants, the contributors look at the value issues entrenched in multiculturalism and the policy challenges and measures adopted to address them.Key features Focuses on 7 European countries: Belgium, Britain, Denmark, France, Germany, Greece and SpainGives an overview of different approaches to multiculturalismLooks at issues of citizenship, diversity, civic recognition, gender, religious diversity & education, integration, anti-discrimination policies and social policyApproaches multiculuralism in 5 waysCharts the legal, political and educational challenges posed by migration-related religious, ethnic and cultural diversity in European countriesApplies political theory to these practical challenges and the value systems involved Assesses the policy solutions adopted in different countriesCompares different policies and models, and how they are implementedDiscusses whether all solutions are bound in their national contexts or whether they are relevant across Europe